Asymmetric development of the nervous system. Issue 1 (13th October 2017) - Alqadah, Amel; Hsieh, Yi‐Wen; Morrissey, Zachery D.; Chuang, Chiou‐Fen
Abstract : The human nervous system consists of seemingly symmetric left and right halves. However, closer observation of the brain reveals anatomical and functional lateralization. Defects in brain asymmetry correlate with several neurological disorders, yet our understanding of the mechanisms used to establish lateralization in the human central nervous system is extremely limited. Here, we review left‐right asymmetries within the nervous system of humans and several model organisms, including rodents, Zebrafish, chickens, Xenopus, Drosophila, and the nematode Caenorhabditis elegans . Comparing and contrasting mechanisms used to develop left‐right asymmetry in the nervous system can provide insight into how the human brain is lateralized. Developmental Dynamics 247:124–137, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Similarities and differences are found in the molecular mechanisms used to establish left‐right asymmetry in the nervous system of different animal species. There are conflicting reports in the human brain asymmetry field that may limit advances in determining molecular mechanisms used for brain laterality. Functional and anatomical brain asymmetries may use distinct molecular mechanisms. Aspects of sensory perception of the environment requires asymmetry in the nervous system. Similarities are observed between mechanisms used to establish left‐right patterning of the nervous system and visceral organs.